HUBUNGAN TINGKAT KEPATUHAN DIET DAN STATUS GIZI PADA PASIEN RAWAT JALAN DISPEPSIA DI RSUD dr. H. CHASAN BOESOIRIE TERNATE: HUBUNGAN TINGKAT KEPATUHAN DIET DAN STATUS GIZI PADA PASIEN RAWAT JALAN DISPEPSIA DI RSUD dr. H. CHASAN BOESOIRIE TERNATE - Fahmi Abdul Hamid; Nizmawaty Amra (Jurnal Kesehatan, 2014)
Abstract : Dyspepsia is a collection of complaints / clinical symptoms consist of pain in the upper abdomen persistent or relapsing. In 2004, dyspepsia ranks 15th on the list of 50 diseases with the highest hospitalization respondents in Indonesia with a proportion of 1.3% and ranks 35th of the 50 leading causes of death. From the research, it was found that of the 171 public hospitals in Indonesia, there are 40% of respondents stated that the food provided does not meet the nutritional adequacy. Other studies mention of 10 Hospitals in Jakarta, as many as 797 respondents (43%) stated that the quality of food served poorly. Based on research conducted at the General Hospital of dr. H. Chasan Boesoirie Ternate In 2010, the prevalence of dyspepsia incidence rate for inpatient 512 respondents (11%), outpatient 571 respondents (12.27%). While in 2011 the rate of prevalence of dyspepsia to hospitalization 752 respondents (18%) and outpatient 961 respondents (23%). This type of research is penilitian deskiptif corelational analytic approach to study and look at the relationship between diet and nutritional status of compliance. This research was conducted in respondents Dyspepsia in hospital outpatient dr.H.Chasan Boesoirie Ternate for 3 months, ie from July to September 2013. The population in this study were all respondents in the hospital outpatient dyspepsia. dr. H. Chasan Boesoirie Ternate. (100%) of the respondents of people with dyspepsia do not adhere to the recommended diet. Most respondents of people with dyspepsia have a normal nutritional satus based (IMT) (55.6%). There is a significant association between diet and nutritional status of compliance with rhit value 0.518> 0.38 rtabel singnifikan at the level of 0.001 <0.5.